Hemispheric specialization and laterality studies - Cantú Cervantes, Daniel (Universidad Autónoma de Tamaulipas, 2017)
The idea of laterality is related to those investigations and studies on the cognitive aspects of left and right handed people. The findings in this regard have clarified the current conception about the knowledge of the hemispheric function and its impact on mental flexibility, attention and information processing. The purpose of this review is to provide an overview of hemispheric specialization and its relation to related aspects such as ambidextrism, laterality, memory, language, emotion, holistic and focused information processing, musical aspect, Creativity, divergent thinking, the etiology of lefty, Bilingualism and cognitive complementarity. The conclusions show that while the cerebral hemispheres are physically divided, they show specializations in coordinated cognitive tasks in a complementary participation.